The Maintaining of Trust of Online Business Trading from Islamic Perspective - Rahmayanti, Rima; Ramdan Padmakusumah, Rizal; Susanti, Neneng; R. , Susanto (International Journal of Psychosocial Rehabilitation, 2020)
Based on country general managerin 2018 reveals that customer satisfaction online shopping decreased until 86% because the items that the buyer received were not the same as what on display or the items that they buy are expectations, as well as the Digital Trust Index survey explains the rampant digital fraud that has reduced consumer confidence in shopping online. The purpose of this study is to find out about the Islamic perspective of the importance of maintaining trust in trading online, which is based on Islamic Shari'a. The research method used is descriptive-qualitative. The results of this study are that online businesses must be trustworthy in maintaining consumer trust by holding the principle of Islamic Shari'a, including: not reducing the weight of the scale, explaining the specifications of the products sold, and not over-editing images that do not match the original form.